The Many Faces of Amyloid β in Alzheimer's Disease - Chiang, Peter K.; Lam, Michael A.; Luo, Yuan (Current Molecular Medicine, 2008)
The ‘amyloid cascade hypothesis’ links amyloid β peptide (Aβ) with the pathological process of Alzheimer's disease (AD) and it still awaits universal acceptance. Amyloid precursor protein (APP), through the actions of the β-secretase complex, eventually becomes a different Aβ species. The various Aβ species have proven to be difficult to investigate under physiological conditions, and the species of Aβ responsible for neurotoxicity has yet to be unequivocally identified. The two important Aβ peptides involved are Aβ1-40 and Aβ1-42, and each has been ascribed both toxic and beneficial attributes. The ratio between the two species can be important in AD etiology. Additionally, shorter variants of Aβ peptides such as Aβ1-8, Aβ9-16 and Aβ16 have also been shown to be potential participants in AD pathology. Interestingly, a new 56-kDa Aβ peptide (Aβ*56) disrupts memory when injected into the brains of young rats. Transgenic mice models are complicated by the interplay between various human Aβ types and the mouse Aβ types in the mouse brains. However, the accumulation of Aβ1-42 in the brains of transgenic C. elegans worms and Drosophila is indeed detrimental. A less investigated aspect of AD is epigenetics, but in time the investigation of the role of epigenetics in AD may add to our understanding of the development of AD.
Keywords: C. elegans